Hubungan Identitas Profesional dan Motivasi pada Mahasiswa Pendidikan Dokter Tahun Pertama di Fakultas Kedokteran Universitas Sam Ratulangi - Rasyid, Rifat Rasendriya; Wungouw, Herlina Ineke Surjanne; Berhimpon, Siemona Lydia Eunike (Jurnal Pendidikan Indonesia, 2025)
Background and Aims: Professional identity is the key to professionalism and a characteristic of health services. Having a good professional identity will be in line with the increase in patient safety and the formation of professional identity has been found to have a positive correlation with motivation. The highs and lows of motivation in students in learning can have an impact on the learning process and achievement results and are influenced by several factors such as age, gender, and the length of the gap year. Purpose: This study aims to determine the correlation between professional identity and motivation in first-year medical students at the Faculty of Medicine, Sam Ratulangi University. Methods: This research uses a quantitative method with analytic-observational studies with cross-sectional methods that are conducted on 236 first-year medical students at the Faculty of Medicine, Sam Ratulangi University, and are analyzed using Spearman Correlation to determine the bivariate correlation between professional identity and motivation. Result: A total of 210 of 236 subjects who met the eligibility criteria were included in this study. The majority of subjects (n=155, 73.8%) were female, the average age of the subjects was 18 years, and the duration of the gap year of subjects was 0 years (n=169, 80.5%). The professional identity of the majority of subjects was found good (n=195, 92.9%) and motivation was found to be high-moderate in the majority of subjects (x̄=55.9, Med=56). Bivariate tests were analyzed using Spearman correlation and obtained a value of rs = 0.503 (p<0.001).Conclusion: There is a positive and significant correlation between professional identity and motivation among first-year medical students in the Faculty of Medicine, Sam Ratulangi University.